(untitled) (Bangladesh Journal of Neuroscience, 2013)
Background & Objectives: Thoraco-lumbar fracture is one of the common problems in spinal injury patients. Its early management can prevent complication after injury and can improve neurological function. The treatment plan of unstable fracture is controversial. Methods: The study was carried out at the department of neurosurgery, Bangabandhu Sheikh Mujib Medical University from June 2010 to July 2011 among the patients admitted with thoraco-lumbar spine fracture. Results: A total number of 15 patients with thoracolumbar spine fracture were included in the study. Among the 15 patients, 13(86.66%) were male. The highest number of patients were in age group of 1-20(40%) and 21-40(40%) years. The commonest cause of Thoraco-lumbar spine injuries were fall from height which was 8(53.33%) in number. The commonest site of injury was L1 fracture in 4(60%) patients. It was documented that bladder dysfunction and lower limb weakness were the commonest sign. It was evident that, 10(66.70%) and 4(26.66%) of the patients were partially and completely improved after surgery respectively and 3(10%) of patients had wound infection. Conclusion: Thoraco-lumbar spine fracture with incomplete injury, early surgery can improve many of the patients life. DOI: http://dx.doi.org/10.3329/bjn.v28i2.17181 Bangladesh Journal of Neuroscience 2012; Vol. 28 (2): 102-107